2019
DOI: 10.1021/acs.jpcc.9b02704
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the Microstructure of Donor/Acceptor Blend Films To Achieve High-Performance Ternary Data-Storage Devices

Abstract: Most of the high-performance electronic devices are based on donor–acceptor (D–A) structured molecules, which usually require complex reaction conditions and long-time synthesis periodicity, limiting the large-scale potential application in future. Encouraged by our previous research about blending the pristine electron-donor and electron-acceptor together as the active layer in memory devices, the tailor-made D/A blends with large π-conjugated planarity were designed for effective molecular interactions in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Figure 4c further shows that the diffraction peak intensity remains unchanged with the increase of LB film layers, which shows that the molecular stacking directions in LB films with different layers are completely consistent. This orderly intermolecular arrangement and layered stacking are conducive to the formation of efficient charge transmission in the films, and play an important role in reducing device energy consumption and improving device stability [8a,11] …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 4c further shows that the diffraction peak intensity remains unchanged with the increase of LB film layers, which shows that the molecular stacking directions in LB films with different layers are completely consistent. This orderly intermolecular arrangement and layered stacking are conducive to the formation of efficient charge transmission in the films, and play an important role in reducing device energy consumption and improving device stability [8a,11] …”
Section: Resultsmentioning
confidence: 99%
“…Whereas the blue parts represent the negative electrostatic potential of the NA−Py molecule which mainly attributed to the electron acceptor of naphthimide and pyridine groups (Figure 7b). These negative regions could act as acceptors to hinder the free movement of charge carriers in the films [11,16] …”
Section: Resultsmentioning
confidence: 99%
“…Though, with the increasing C12-PTCDI portion (1/2 and 1/3), the XRD analysis exhibited peaks consistent with the thin film of pristine A . Thus signifies a desired long-range ordering of the A in blends, that is mostly brought by the more amounts of branched alkyl chains with a large steric hindrance that prevented the ordered stacking of D 47 . Overall the crystallinity is reserved in BHJ blended films.…”
Section: Resultsmentioning
confidence: 99%
“… 48 Miao et al simply blended a donor of tri‐carbazole (TCz) with an acceptor of perylenediimide (PDI) and found that the MIM‐type ITO/TCz:PDI/Al devices displayed tunable resistive memory behaviors from volatility to nonvolatility as the D / A blending ratio varies (5:1, 2:1, 1:1, and 1:2) 103 . Zhu et al from the same group utilized a similar strategy of blending donor of indolo[3,2‐ b ]carbazole (ICz) with PDI acceptor (ICz:PDI = 2:1, 1:1, and 1:2), and the resistive memory behaviors were modulated from binary to ternary through the interactive coupling between the donor and acceptor, which was confirmed by the UV‐vis spectroscopy and CV test of the blending films 104 …”
Section: Organic Small Molecule‐based Materials For Resistive Memorymentioning
confidence: 95%
“…Extensive studies have revealed that organic small molecules could be applied as excellent resistive memory materials, attributing to their advantages of low cost, light weight, mechanical flexibility, and ease of processing 47,48,66,70,83‐104 . Many organic small molecules have been reported to exhibit resistive switching characteristics, including the binary and even higher multilevel nature 70,83‐96,105,106 .…”
Section: Organic Small Molecule‐based Materials For Resistive Memorymentioning
confidence: 99%